Ambientalismo em João Pessoa/PB: A participação da sociedade nas políticas públicas (2005-2012) - Castro, Vivian Maitê (2013)
João Pessoa is one of the few Brazilian capitals where there still remain significant preserved areas of Atlantic Coastal Rainforest, and the local environmental movement has won important causes that contributed to this difference, however today it can count on a few activists. Meanwhile, the crisis of representative democracy, and the demand for a political project with greater participation of society, has increased across the country. In João Pessoa, even though the municipality initiated instances of participation, the government is in a hybrid process of transformation between the traditional and authoritarian government with hierarchical relationships and vertical dominance of technocracy; and the innovative model of government with decentralized horizontal relationships, and constant dialogue with society. In this context, the present study aimed to investigate the relationship of environmental NGOs with the local government in the formulation of public policies on the environment. Through a quantitative and qualitative study, the research sought to examine, from the government's official discourse on NGOs, and their self perception, how this relationship and dialogue relates to building a participatory democracy.